Research on Key Technologies of TD-LTE-Advanced - Jianhui Mao; Wei Deng; Guang Yang (Dianxin kexue)
The carrier aggregation and enhanced MIMO for enhancing throughout,CoMP and eICIC for interference suppression,eSON for improving SON efficiency were introduced in detail. The technology industry status, simulation and test results were also described.